Mild and efficient synthesis and base-promoted rearrangement of novel isoxazolo[4,5-b]pyridines - Nikol’skiy, Vladislav V.; Minyaev, Mikhail E.; Bastrakov, Maxim A.; Starosotnikov, Alexey M. (Beilstein Journal of Organic Chemistry, 2024)
An efficient method for the synthesis of isoxazolo[4,5-b]pyridines has been developed on the basis of readily available 2-chloro-3-nitropyridines via the intramolecular nucleophilic substitution of the nitro group as a key step. The previously unknown base-promoted Boulton–Katritzky rearrangement of isoxazolo[4,5-b]pyridine-3-carbaldehyde arylhydrazones into 3-hydroxy-2-(2-aryl[1,2,3]triazol-4-yl)pyridines was observed.
Keywords: aromatic nitro compounds; Boulton–Katritzky rearrangement; isoxazolo[4,5-b]pyridines; nucleophilic substitution; 1,2,3-triazoles